Disentangling divergent factors controlling bacterial and fungal communities in topsoil and subsoil horizons across environmental gradients of tropical volcanic regions - Han Lyu; Kozue Sawada; Ruohan Zhong; Method Kilasara; Arief Hartono; Randy A. Dahlgren; Shinya Funakawa; Tetsuhiro Watanabe (CATENA, 2024)

Cropland intensification mediates the radiative balance of greenhouse gas emissions and soil carbon sequestration in maize systems of sub‐Saharan Africa - Jinsen Zheng; Alberto Canarini; Kazumichi Fujii; William N. Mmari; Method M. Kilasara; Shinya Funakawa (Global Change Biology, 2023)
Sub‐Saharan Africa (SSA) must undertake proper cropland intensification for higher crop yields while minimizing climate impacts. Unfortunately, no studies have simultaneously quantified greenhouse gas (GHG; CO 2 , CH 4 , and N 2 O) emissions and soil organic carbon (SOC) change in SSA croplands, leaving it a blind spot in the accounting of global warming potential (GWP). Here, based on 2‐year field monitoring of soil emissions of CO 2 , CH 4 , and N 2 O, as well as SOC changes in two contrasting soil types (sandy vs. clayey), we provided the first, full accounting of GWP for maize systems in response to cropland intensifications (increasing nitrogen rates and in combination with crop residue return) in SSA. To corroborate our field observations on SOC change (i.e., 2‐year, a short duration), we implemented a process‐oriented model parameterized with field data to simulate SOC dynamic over time. We further tested the generality of our findings by including a literature synthesis of SOC change across maize‐based systems in SSA. We found that nitrogen application reduced SOC loss, likely through increased biomass yield and consequently belowground carbon allocation. Residue return switched the direction of SOC change from loss to gain; such a benefit (SOC sequestration) was not compromised by CH 4 emissions (negligible) nor outweighed by the amplified N 2 O emissions, and contributed to negative net GWP. Overall, we show encouraging results that, combining residue and fertilizer‐nitrogen input allowed for sequestering 82–284 kg of CO 2 ‐eq per Mg of maize grain produced across two soils. All analyses pointed to an advantage of sandy over clayey soils in achieving higher SOC sequestration targets, and thus call for a re‐evaluation on the potential of sandy soils in SOC sequestration across SSA croplands. Our findings carry important implications for developing viable intensification practices for SSA croplands in mitigating climate change while securing food production.

Central roles of livestock and land-use in soil fertility of traditional homegardens on Mount Kilimanjaro - Yuri Ichinose; Tomohiro Nishigaki; Method Kilasara; Shinya Funakawa (Agroforestry Systems, 2020)

Nitrogen availability to maize as affected by fertilizer application and soil type in the Tanzanian highlands - Jinsen Zheng; William N. Mmari; Tomohiro Nishigaki; Method M. Kilasara; Shinya Funakawa (Nutrient Cycling in Agroecosystems, 2018)

Ammonia volatilization following urea application at maize fields in the East African highlands with different soil properties - Jinsen Zheng; Method M. Kilasara; William N. Mmari; Shinya Funakawa (Biology and Fertility of Soils, 2018)

Effects of different phosphorus-efficient legumes and soil texture on fractionated rhizosphere soil phosphorus of strongly weathered soils - Soh Sugihara; Yutaro Tomita; Tomohiro Nishigaki; Method Kilasara; Jun Wasaki; Shinya Funakawa (Biology and Fertility of Soils, 2016)